STUDY ON CONSTRUCTION CONTRACT PRICE ADJUSTMENT AS APPLIED TO CIVIL ENGINEERING PROJECTS - Gana, A.J.; Okoye, S.S.C.; Braimoh, O.S (BW Academic Journal, 2022)
Conditions of contract and price adjustment Issue are major aspect in the construction Industry. Contract conditions, which is also known as contract problems provisions and price adjustment problem are known to be unavoidable during the execution of construction contract, and the problems becomes even horst when price adjustment is put in practice. This study examines different ways of making price adjustment, Basic of construction price index, the challenges in price adjustment practices, merits and demerits of price adjustment as it related to civil engineering construction projects.